Editorial: paradoxical skin lesions during anti‐TNF treatment—an additional argument to consider new biologics as first line therapy in inflammatory bowel disease. Issue 6 (21st August 2018) - Pariente, B.; Blondeaux, A.
Abstract : This article is linked to Bae et al and Lee et al papers. To view these articles visithttps://doi.org/10.1111/apt.14822 andhttps://doi.org/10.1111/apt.14917 .